c-MYC and Epithelial Ovarian Cancer - Reyes-González, Jeyshka M.; Vivas-Mejía, Pablo E. (Frontiers in Oncology, 2021)
Ovarian cancer is the deadliest of gynecological malignancies with approximately 49% of women surviving five years after initial diagnosis. The standard of care for ovarian cancer consists of cytoreductive surgery followed by platinum-based combination chemotherapy. Unfortunately, despite initial response, platinum resistance remains a major clinical challenge. Therefore, the identification of effective biomarkers and therapeutic targets is crucial to guide therapy regimen, maximize clinical benefit, and improve patient outcome. Given the pivotal role of c-MYC deregulation in most tumor types, including ovarian cancer, assessment of c-MYC biological and clinical relevance is essential. Here, we briefly describe the frequency of c-MYC deregulation in ovarian cancer and the consequences of its targeting.